THE RELATIONSHIP BETWEEN BANK FINANCING AND ECONOMIC GROWTH IN TUNISIA: MULTIVARIATE CAUSALITY ANALYSIS - Lamine Belhouchet, Mohamed; Ahmed, Elhamza (The journal of contemporary issues in business and government, 2024)
This study aimed to test the long-term causality relationship between bank financing and economic growth in Tunisia during the period from 1980 to 2020. It employed the Toda & Yamamoto (1995) methodology, which is based on the developed Augmented VAR model. The study concluded that there is a bidirectional causal relationship between bank financing and economic growth. Therefore, bank financing is one of the causes leading to economic growth in Tunisia, aligning with most economic theories like those of Schumpeter (1911), Hicks (1969), Goldsmith (1969), McKinnon (1973), Shaw (1973), Fry (1988), Levine & King (1993), and Levine (1997). According to Patrick (1966), Tunisia is considered to be in the advanced stages of development because financial development follows economic growth and not vice versa (the demand-following phenomenon).